Alternative Dispute Resolution of Lonto Lèok in Resolving Land Rights Disputes in Deno Village East Manggarai District - Stefanus Don Rade; Nataly Silviana Dewi; Elias Bertolomeus Neu Roga; Benediktus Peter Lay (Journal of Law, Politic and Humanities, 2025)
This paper discusses the existence of Lonto Lèok local wisdom as an alternative in resolving disputes over land rights status in Deno Village, South Lamba Leda District, East Manggarai Regency, East Nusa Tenggara. This research aims to identify the history of land disputes, as well as understand the application of Lonto Lèok in resolving conflicts. The method used is a case study with a qualitative approach, including in-depth interviews, participatory observation, and documentation studies. The results showed that Lonto Lèok is still relevant in Manggarai society, functioning as a forum for deliberation to reach a binding agreement. This process not only strengthens social relations, but also creates a peaceful atmosphere in dispute resolution, prioritizing family values and unity. Therefore, the revitalization of Lonto Lèok is necessary to face modern challenges, ensuring that local wisdom values remain alive and functioning in the evolving social context